2007
DOI: 10.1038/emm.2007.4
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HIV-1 Tat enhances monocyte adhesion by up-regulation of ICAM-1 and VCAM-1 gene expression via ROS-dependent NF-κB activation in astrocytes

Abstract: One of characteristic features of AIDS-related encephalitis and dementia is the infiltration of monocytes into the CNS. HIV-1 Tat was demonstrated to facilitate monocyte entry into the CNS. In this study, we examined the effect of HIV-1 Tat on the expression of adhesion molecules, generation of reactive oxygen species (ROS) and NF-κB activation in CRT-MG human astroglioma cells. Treatment of CRT-MG cells with HIV-1 Tat protein significantly increased protein and mRNA levels of ICAM-1 and VCAM-1, as measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…We showed that rutin attenuated ROS production by RANKL or RANKL/TNF and reduced NF-κB activation in osteoclast precursor cells. The involvement of ROS in NF-κB activation has also been demonstrated in other cell types (Schreck et al, 1991;Rhee, 1999;Droge, 2002;Song et al, 2007). Since NF-κB activation is critical for RANKL-induced osteoclastogenesis, it is plausible that the inhibitory effect of rutin on osteoclastogenesis should be mediated by suppression of NF-κB activation.…”
Section: Discussionmentioning
confidence: 98%
“…We showed that rutin attenuated ROS production by RANKL or RANKL/TNF and reduced NF-κB activation in osteoclast precursor cells. The involvement of ROS in NF-κB activation has also been demonstrated in other cell types (Schreck et al, 1991;Rhee, 1999;Droge, 2002;Song et al, 2007). Since NF-κB activation is critical for RANKL-induced osteoclastogenesis, it is plausible that the inhibitory effect of rutin on osteoclastogenesis should be mediated by suppression of NF-κB activation.…”
Section: Discussionmentioning
confidence: 98%
“…ously, CREB transcription factor undergoes activation by PKAdependent phosphorylation on Ser 133 (42), whereas p65 NF-kB RelA is phosphorylated by PKA on Ser 276 (42,43) or by a redoxsensitive mechanism on Ser 536 (44)(45)(46). The present study demonstrates a PKA-dependent phosphorylation of CREB on Ser 133 at 10 h and two events of phosphorylation of p65 NF-kB on Ser 536 at 1 h and 8-10 h of TNF-a exposure, whereas phosphorylation of p65 NF-kB Ser 276 was not detected under these conditions, suggesting that PKA is not involved in NF-kB activation.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of astrocytes with HIV-1 Tat resulted in activation of NF-κB which was responsible for up-regulation of various cytokines, chemokines and adhesion molecules (Nicolini et al, 2001;Song et al, 2007). Although the mechanisms of Tat-mediated NF-κB activation remain to be elucidated, several studies have implicated the in-volvement of Tat-induced oxidative stress (Bruce- Keller et al, 2001;Song et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms of Tat-mediated NF-κB activation remain to be elucidated, several studies have implicated the in-volvement of Tat-induced oxidative stress (Bruce- Keller et al, 2001;Song et al, 2007). HIV-1 Tat can increase levels of reactive oxygen species (ROS) directly and indirectly which in turn activates NF-κB, a redox-sensitive transcriptional factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation